Landasan Filosofis Pendidikan Islam dalam Pemikiran Imam Al-Ghazali dan Ibnu Taimiyah: The Philosophical Foundations of Islamic Education in the Thought of Imam Al-Ghazali and Ibn Taymiyyah - Zubair Qudsi El Hanif; Abdul Hayyie Al-Kattani; Akhmad Alim; Muhammad Adib Irfan; Muhammad Fadhlan (Tasfiyah: Jurnal Pemikiran Islam, 2025)
This study compares the educational thinking of Al-Ghazali and Ibn Taymiyyah, two prominent figures in Islamic history. It employs a qualitative approach based on literature review (library research) and uses a comparative method to analyze the educational thought of both scholars. Despite their methodological differences, both thinkers share a fundamental objective: attaining eternal happiness in the afterlife through beneficial knowledge and righteous action, with an emphasis on the purification of the heart. Al-Ghazali emphasizes a Sufi-oriented approach, particularly through the concepts of takhalli (self-purification) and tajalli (divine manifestation). In contrast, Ibn Taymiyyah adopts a more rational and scientific framework, focusing on the ‘ilmiyyah approach to prevent intellectual deviations (shubuhāt) and the irādiyyah approach to restrain base desires (shahawāt). Despite differences in methodology, both agreed on the goal of education to shape individuals and societies in harmony with the Qur'an and Sunnah. This study concludes that their ideas complement each other and can be applied in contemporary education to integrate cognitive and affective aspects.